Decision-making and ethical considerations in ventilatory support in critical hospital areas in the context of the COVID-19 pandemic - Amado-Tineo, José Percy (2021)
Objetive. Hospital resources are insufficient given the demand for seriously ill patients with COVID-19. Proper resource management is essential to provide the best possible care. Criteria to help make appropriate and timely decisions were reviewed, following ethical principles. The prioritization of invasive ventilatory support must be done in a transparent and objective manner, comprehensively evaluating the patient and based on objective criteria such as prognostic scales, life cycle or clinical commitment. Symptomatic treatment (including palliative care) is essential in this pandemic and communication with the patient or family makes it possible to humanize the care of health personnel.